Motivational Dynamics as Mediation: The Influence of Leadership and Organizational Culture on Employee Performance - Niswatin, Niswatin; Soelistya, Djoko (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
This research was conducted to examine things that influence the influence of leadership and organizational culture on employee performance through motivation as an intervening mediation in banking companies. The type of research used in this research is quantitative research with the population and sample in this research being company employees totaling 65 respondents. The results of the research show that leadership and work culture do not have a positive and significant direct influence, while leadership and work culture have a positive and significant direct influence, and motivation has a positive and significant direct influence, as well as the indirect influence of leadership and work culture on performance. through motivation it has a positive influence and motivation is full mediation. Therefore, seeing the importance of motivation as mediation, companies must always pay attention to employees in providing direct and indirect allowance facilities.